Analysis of Buddhist Concepts in the Context of Buddhist Economic Theory (Pashupati Pragya पशुपति प्रज्ञा, 2025)
Buddhist economics is an approach to economics that is both philosophical and spiritual. It looks at how emotions affect economic behaviour and how the human mind functions. Numerous political and socioeconomic specialists have expressed conflicting opinions regarding the relationship between Buddhism and economics. Buddhism views economics as a means of achieving the common goals of environmental, personal, and societal well-being. Economics is part of a more significant effort to solve humanity's problems. This work has clarified material on Buddhist economic theory that may be found in the Tripitaka, specifically in the Sutra Pitaka and the Vinaya Pitaka. It examines how the core teachings of Buddhism influence an individual's socioeconomic behaviour. It is investigated using hypotheses put forth by many academics.